PENGELOLAAN SAPTA PESONA PADA WISATA TAMAN LAUT PULAU POMBO KABUPATEN MALUKU TENGAH - Kesya Pattimukay; Angela Ruban; Yofita Anaktototy (Universitas Pattimura, 2023)
The purpose of this study is to describe management related to planning, organizing, and supervising of Sapta Pesona in the Marine Natural Tourism Park Pombo Island, Central Maluku District which includes: security, order, beauty, cleanliness, coolness, friendliness, and memory. This research uses a descriptive approach with qualitative data. Data collection techniques were carried out by survey, interview, and observation methods. The sample selection was carried out using a purposive sampling method involving 3 employees of the Maluku Natural Resources Conservation Agency, 3 speedboat owners, and 4 people who are members of the community around Pombo Island, namely 2 people from Waai Village and 2 people from Tulehu Village. These two villages are villages that have access to Pombo Island. Research data were analyzed by data reduction, data presentation, and conclusion. The results of this study indicate that: 1). Security is not good because there are no security officers either on the coast or in the Pombo Island area; 2). Orderliness is not good enough because there is no pier as a place to drop off tourists or a berth for used transportation; 3). The lack of facilities and infrastructure to support beauty and the lack of cleanliness in the tourist area makes the tourist object less beautiful; 4). The tourist attraction of Pombo Island is not clean because there is a lot of scattered garbage, and the lack of existing cleaning support facilities, such as the absence of a cleaning manager and no garbage disposal; 5). The Pombo Island tourism object is quite cool, but there are no facilities and infrastructure to support coolness because there is no resting place for tourists such as a gazebo; 6). the community which is the access point for heading to Pombo Island is quite good and friendly to tourists, especially in providing information for tourists; dan 7). Currently there is no provision of regional souvenirs for tourists, and regarding the activities of a particular event at a tourist attraction, beach parties are routinely held every year.